Gaudy night - Sayers, Dorothy L. (Dorothy Leigh), 1893-1957. (London : Hodder and Stoughton : New English Library, 2003)
Harriet Vane finds herself trapped in a web of romance and terror when her attendance at Oxford is marred by a series of bizarre, threatening pranks.
Adult.
Adult
Keywords: Private investigators -- England -- Oxford -- Fiction; Vane, Harriet (Fictitious character) -- Fiction; Wimsey, Peter, Lord (Fictitious character) -- Fiction; Women detectives -- England -- Oxford -- Fiction; Mystery fiction; Private investigators -- Fiction; Vane, Harriet (Fictional character) -- Fiction; Wimsey, Peter, Lord (Fictional character) -- Fiction; Women detectives -- Fiction; Oxford (England) -- Fiction; Oxford (England) -- Fiction